2011
DOI: 10.2472/jsms.60.976
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Zinc Oxide Nanorods Via Aqueous Solution Process and Their Application for Biosensors

Abstract: ZnO nanorods were grown on various substrates using aqueous solution, aiming at integrating with bio− or organic− molecular structures assembled by bottom-up process. ZnO nanorods with the average diameter of 100 nm and the height of 1.5μm were obtained on an Au/Ti/Si (111) substrate via microwave heating, which is an environmental harmonized system allowing fast heating. Aggregation of ZnO nanorods occurred on a single crystalline ZnMgO film and growth mechanism of ZnO nanorods was discussed. Using ZnO nanoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In addition to that, they can be obtained with various growth methods, i.e., not only vacuum-based techniques but also solution-based ones at low temperatures. Recently, we have successfully fabricated amperometric glucose sensors using aqueous grown ZnO nanorod arrays on Au/Ti/Si(111) substrates and reported that the detection limit of glucose was as low as 0.01mM [1]. Considering that the amperometric glucose sensing relies on the detection of the current through the transfer of electrochemically produced electrons at the surface of ZnO nanorods, electronic properties of aqueous grown ZnO nanorods arrays on Au/Ti/Si substrates were investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, they can be obtained with various growth methods, i.e., not only vacuum-based techniques but also solution-based ones at low temperatures. Recently, we have successfully fabricated amperometric glucose sensors using aqueous grown ZnO nanorod arrays on Au/Ti/Si(111) substrates and reported that the detection limit of glucose was as low as 0.01mM [1]. Considering that the amperometric glucose sensing relies on the detection of the current through the transfer of electrochemically produced electrons at the surface of ZnO nanorods, electronic properties of aqueous grown ZnO nanorods arrays on Au/Ti/Si substrates were investigated.…”
mentioning
confidence: 99%
“…Judging from the report on the electron carrier concentration in aqueous grown ZnO nanorods of the order of 10 18 cm -3 by means of time-resolved THz spectroscopy [7], this difference between the top and bottom electrodes would be attributed to the interface properties of aqueous grown ZnO nanorods. Ohmic-like behaviour of the ZnO nanorods/bottom Au film, which is preferable for amperometric biosensing [1], would be originated form the formation of conducting ZnO nucleus at the initial stage of the growth on the bottom Au film, similar to the degenerated layer formation in epitaxial ZnO film/sapphire interface [8]. On the other hands, rectifying behaviour of the top Au electrode/ZnO nanorods can be attributed to the Schottky barrier formation on high quality ZnO [9] in agreement with the I-V characteristics of ZnO nanorods on O-polar ZnO film measured by conductive atomic force microscopy (AFM) [10].…”
mentioning
confidence: 99%